Debunking Delusions: The Inside Story of the Treatment Action Campaign by Nathan Geffen - Bauer, Henry (Journal of Scientific Exploration, 2012)
This book’s lead title seemed to make it a natural for review in the Journal of Scientific Exploration; but it is the subtitle that properly describes the contents: It deals almost exclusively with South African controversies, about HIV/AIDS in particular and medical matters more generally. Still, there are points of general interest. When a belief does not correspond to reality, the believers can go far astray in their actions and their recounting and explicating of events. So it is with this book, which is based on the mistaken notion that a retrovirus designated HIV causes fatal illness—AIDS—by destroying the immune system. Readers should also beware of the frequently used but entirely misleading terms “AIDS denialist” and “AIDS denialism”: No one denies the existence of AIDS. What is denied is that AIDS is a new syndrome and that HIV is its cause. “Cognitive dissonance” refers to the fact of human psychology that makes it essentially impossible for true believers to recognize—to see, to take in—evidence that falsifies their belief. The classic description was by Festinger, Riecken, and Schachter (1956). Cognitive dissonance is rampant among those who have accepted HIV/AIDS theory, and this book illustrates it.